Learning environment and self-directedness of TESL postgraduate students / Noor Atiqah Abdul Basitt - Abdul Basitt, Noor Atiqah (2014)
The study is aimed to identify the characteristics of self-directedness as perceived by postgraduate students, to investigate self-directedness among postgraduate students, and to examine the extent to which learning environments influence postgraduate students’ self-directedness. The study involves 20 semester 1 TESL postgraduate full time students. In conducting the study, the mixed methods design is applied and three sets of instruments are used - questionnaire, interviews, and classroom observations. Interestingly, the study found that the respondents are self-directed and portfay the characteristics of adult learners’ self-directedness. Among the characteristics of selfdirectedness as perceived by the respondents are planning the learning, having learning objectives, good time management, resourcefulness, and problem-solving and decision making abilities. Nonetheless, sometimes the perceived characteristics are negated by the respondents’ actions. Besides, the findings show that the learning environments do influence the postgraduate learners’ self-directedness. It is hoped the study would provide useful insights to improve the existing practice of teaching and learning, employers, and the learners. It is also recommended that the learners be mentally prepared for postgraduates expectations, and the lecturers apply a variety of teaching practices to adapt to the various characteristics of self-directedness.